Impact of Extractive Industries on Environmental Damage in Jambi Province: Ecological and Social Analysis - Suci Rahmadani (JURNAL ILMIAH DETUBUYA, 2025)
This study aims to analyze the impact of extractive industries on environmental damage in Jambi Province from an ecological and social perspective. Extractive industries, such as coal mining, petroleum, and palm oil plantations, contribute to land degradation, deforestation, water and air pollution, and changes in the social conditions of local communities. This study uses a qualitative approach with library research methods, reviewing literature, government reports, scientific journals, and documents related to the extractive industry in Jambi. The analysis was conducted descriptively and critically to identify the overall ecological and social impacts. The results show that extractive industry activities cause environmental damage and lead to significant changes in livelihoods, lifestyles, and land conflicts in communities. Therefore, this study is important as a basis for recommendations for sustainable and equitable natural resource management.